Cytomegalovirus in children undergoing haematopoietic stem cell transplantation: a diagnostic and therapeutic approach to antiviral resistance - Hume, Jocelyn; Sweeney, Emma L.; Lowry, Kym; Fraser, Chris; Clark, Julia E.; Whiley, David M.; Irwin, Adam D. (Frontiers in Pediatrics, 2023)
Cytomegalovirus (CMV) is a ubiquitous virus which causes a mild illness in healthy individuals. In immunocompromised individuals, such as children receiving haematopoietic stem cell transplantation, CMV can reactivate, causing serious disease and increasing the risk of death. CMV can be effectively treated with antiviral drugs, but antiviral resistance is an increasingly common complication. Available therapies are associated with adverse effects such as bone marrow suppression and renal impairment, making the choice of appropriate treatment challenging. New agents are emerging and require evaluation in children to establish their role. This review will discuss established and emerging diagnostic tools and treatment options for CMV, including antiviral resistant CMV, in children undergoing haematopoietic stem cell transplant.